THEORETICAL AND PRACTICAL SIGNIFICANCE OF THE PRINCIPLE OF THE RULE OF LAW IN THE RULE OF LAW IN THE REPUBLIC OF UZBEKISTAN (International journal of artificial intelligence, 2026)
This article analyzes the role and significance of the rule of law in the process of establishing a legal state from a scientific, theoretical and practical perspective. The concept of the rule of law, its essence as a main feature of a legal state, its significance in society and state governance are highlighted. The theoretical and legal foundations and practical mechanisms of the process of establishing a legal state in the Republic of Uzbekistan are analyzed in depth. The scientific content of the concept of a legal state, its inextricable connection with constitutional principles and its role in the national legal system are revealed. The issues of legislative reforms aimed at forming a legal state in the country, modernization of the judicial and legal system, improvement of human rights protection mechanisms and development of civil society institutions are also analyzed.